Introduction to the study of history = pengantar ilmu sejarah / Charles Seignobos, Charles-Victor Langlois; penerjemah, H. Supriyanto Abdullah; penyunting, Nur Iswarso - SEIGNOBOS, Charles ,1854-1942; Charles-Victor Langlois; Supriyanto Abdullah , H.; Nur Iswarso (Indoliterasi, 2015)
iv, 356 hlm. : ilus. ; 23 cm.